PENGARUH TEKANAN EKSTERNAL, KOMITMEN MANAJEMEN DAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi empiris pada Pemerintahan Kota Bukittinggi) - Yesnita, Mutia; Kurnia, Pipin; ', Desmiyawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this study is to explore the influence of the external pressure, commitment of management and government internal control system to the application management financial transparency reporting. The population in this study were employees who worked in the Bukittinggi city (27 government agencies). The sampling method used in this study is purposive sampling method. The hypotheses then tested by using SPSS 17. The results of this study indicated that the exsternal pressure, management commitment, internal control system significantly affect the transparency of financial reporting. The magnitude of the effect (R2) of the external pressure, commitment of management and government internal control system to the application management financial transparency reporting was 33,3 %. While the remaining 66,7% is influenced by other variables outside the model that has not been included in this study.Keywords: transparency of financial reporting, exsternal pressure, management commitment and internal control system